Faith leaders' messaging is essential to enhance HIV prevention among black Americans: results from the 2016 National Survey on HIV in the black community (NSHBC). - Yusuf Ransome; Laura M. Bogart; Amy S. Nunn; Kenneth H. Mayer; Keron R. Sadler; Bisola O. Ojikutu (BMC, 2018)
Abstract Background To investigate whether religious service attendance and faith leaders' messages about HIV and same-sex relationships are associated with acceptance of HIV prevention strategies. Methods Multivariable Poisson regression assessed whether attending religious services, faith leaders' messages about HIV and same-sex relationships, and supportiveness of those messages were associated with HIV testing, as well as knowledge of and willingness to use pre-exposure prophylaxis (PrEP) among 868 Black Americans [45% men; M (SD) = 34 (9) years-old] in the 2016 National Survey on HIV in the Black Community, USA. Results Participants who reported attending services monthly and/or hearing faith leaders' messages that were supportive of same-sex relationships had a significantly higher likelihood of willingness to use PrEP (adjusted Rate Ratio[ARR] = 1.76; 95% confidence interval [CI] = 1.09, 2.48) and aRR = 2.19; 95% CI = 1.35, 3.55, respectively), independent of HIV risk. Homophobia was significantly associated with higher likelihood of being aware of PrEP and testing for HIV testing in the past 12 months. Conclusions Faith leaders' messaging can influence Black Americans' perceptions and uptake of HIV prevention strategies. Faith institutions and faith leaders should be involved in designing and disseminating HIV prevention strategies.